An Ordinance Concerning Misdemeanors, §§ 14-15, in General Ordinances of the City of New Franklin 49 (1907) - (:unkn) unknown (My University, 1907)
If any person shall carry concealed upon or about his person any deadly or dangerous weapon or shall go into any church or place where people are assembled for religious worship or into any school room or place where people are assembled for educational, literary or social purpose or to any election precinct on any election day or into any court room during the sitting of the court or into any other public assemblage of persons met for any lawful purpose, other than for militia drills or meetings called under the militia law of this state, having upon or about his person any kind of fire arms, bowie-knife, dirk, dagger, slung-shot or other deadly weapon or shall in the presence of one or more persons exhibit any such weapon in a rude, angry or threatening manner or shall have or carry any such weapon upon or about his person when intoxicated or under the influence of intoxicating drinks he shall upon conviction be punished by a fine not less than fifty nor more than two hundred dollars or by imprisonment in the City prison or work house not less than five days nor more than six months or by both such fine and imprisonment.
Keywords: BRANDISHING; CARRY - CONCEALED; SENSITIVE PLACES